Segment III bypass: An Option to Palliate Proximal Biliary Obstruction - Bhandari, Ramesh Singh (Journal of Society of Surgeons of Nepal, 2018)
Introduction: In the era of minimally invasive therapy, endoscopic or interventional radiological techniques have become preferred technique for palliating advanced malignant hilar obstruction due to carcinoma gallbladder or cholangiocarcionmas. However, in selected group of these locally advanced unresectable disease and fit patients, surgical segment III bypass could still be a viable option for palliation.Methods: I retrospectively reviewed the medical records of all the patients of segment III bypass performed over last six years (Oct 2012- May 2018) and analyzed the indication, perioperative morbidity, symptom relief and survival.Results: Total 17 patients underwent palliative biliary bypass over the specified period. Among them 8 patients underwent segment three III biliary bypass for proximal biliary obstruction. Except 1 patient, all segment three bypass were offered to malignant proximal biliary obstruction. One patient developed postoperative sepsis and had mortality on day 7. Symptom relief in the form of relief of pruritus, improved sleep pattern and improved appetite was seen in 5 patients. In remaining 2 patients, the bilirubin didn’t drop to normal level and the symptom reliefs were partial. However, the patient had good satisfaction over not having an external tube attached to their body. Despite the patent anastomosis, failure in dropping bilirubin level significantly was considered due to segmental obstructions. One patient survived for 18months, 1 had follow up to 13 months. Three patients were lost to follow up after 3 months. Two patients had six weeks follow up and were symptomatically doing better.Conclusion: Surgical segment III bypass is still a good option for palliating malignant hilar obstruction in selected group of patients.